Species diversity and relative abundance of understorey bats at Air Hitam Forest Reserve, Selangor, Malaysia - Mohd Azlan, Jayasilan; Sharma, R. S. K.; Zakaria, M. (Malaysian Nature Society, 2000)
A study of understorey bat species' diversity and relative abundance was carried out in Air Hitam Forest Reserve, Selangor, Malaysia. A total of 15 species from nine genera were capture using harp traps and mist nets during 35 sampling nights. This represents approximately 16 per cent of the total chiropteran fauna known to occur in Peninsular Malaysia. Capture rates were at 0.11 bats per net-night and 1.8 bats per trap-night. Only two pteropodid bat species, accounting for 21.1 per cent of the total capture, were recorded in the forest understorey. The most frequently caught species was Hipposideros cervinus followed by Cynopterus brachyotis, which comprised 59.8 per cent and 16.3 per cent of the total captures, respectively. A low relative abundance was observed for nine entomophagous species which were represented by three or less captures. The daily species accumulation curve showed signs of levelling out to reach an asymptote as early as the tenth capture night, suggesting that additional effort may not yield many more species in the forest understorey. Although little is known about the response of bats to logging, it is suggested that this forest reserve, which has a history of logging and silviculture, may have lost much of its chiropteran diversity. As this study was concentrated in the understorey, additional trapping in the forest canopy and sub-canopy will be necessary to confirm our findings.